Parasitic infections: A new frontier for PGD2 functions - Bruno L. Diaz; Christianne Bandeira-Melo (Current Research in Immunology)
Prostaglandin (PG)D2 is produced and/or triggered by different parasites to modulate the course of the infection. These findings position PGD2 as a therapeutic target and suggest potential beneficial effects of repositioned drugs that target its synthesis or receptor engagement. However, recent in vivo data may suggest a more nuanced role and warrants further investigation of the role of PGD2 during the full course and complexity of parasitic infections.